Curcumin: A multifunctional molecule for the development of smart and active biodegradable polymer-based films - Oliveira Filho, Josemar Gonçalves de [UNESP]; Bertolo, Mirella Romanelli Vicente; Rodrigues, Murilo Álison Vigilato; Marangon, Crisiane Aparecida; Silva, Guilherme da Cruz; Odoni, Fernanda Campos Alencar [UNESP]; Egea, Mariana Buranelo (Elsevier, 2021)
Background: Curcumin is an important phenolic compound extracted from turmeric rhizomes (Curcuma longa Linn.) and is widely used as a natural food dye. This natural pigment has several beneficial health effects, such as antioxidant, antimicrobial, and anti-inflammatory activities. Furthermore, curcumin is highly sensitive in detecting acid-base reactions and can be used as a pH indicator to monitor food quality and applied as a biosensor in packaging. There is a growing concern about the environmental impacts of disposing of plastic food packaging, which has led to the emergence of natural packaging materials in the market that is biodegradable and edible. Scope and approach: This review summarizes the current research on the use of curcumin as a powerful compound for the development of biodegradable and edible food packaging films with smart and active functions. Key Findings and Conclusions: The results from various studies show that curcumin is a multifunctional molecule and can successfully be exploited for application in all types of food packaging. Material developed using curcumin can be a smart package used to monitor the quality of food products such as meat, seafood, and beverages or active packaging can exhibit antioxidant and antimicrobial activities that are capable of improving the quality and conservation of food products.
Keywords: Biosensors; Curcuma longa; Food packaging; Nanocomposites; Turmeric